2014
DOI: 10.7567/apex.7.067301
|View full text |Cite
|
Sign up to set email alerts
|

Novel photoexcitation method for light-addressable potentiometric sensor with higher spatial resolution

Abstract: A novel photoexcitation method for the light-addressable potentiometric sensor (LAPS) is proposed to achieve a higher spatial resolution of chemical images. The proposed method employs a combined light source that consists of a modulated light probe, which generates the alternating photocurrent signal, and a ring of constant illumination surrounding it. The constant illumination generates a sheath of carriers with increased concentration which suppresses the spread of photocarriers by enhanced recombination. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Theoretical analysis and LAPS device simulation have been developed continuously alongside experimental techniques to improve the lateral resolution 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] . The spatial resolution in LAPS is limited by the diffusion of minority charge carriers out of the illuminated region, which depends on the size of illuminated area and the average effective diffusion length of minority charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical analysis and LAPS device simulation have been developed continuously alongside experimental techniques to improve the lateral resolution 11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] . The spatial resolution in LAPS is limited by the diffusion of minority charge carriers out of the illuminated region, which depends on the size of illuminated area and the average effective diffusion length of minority charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a drop of the photocurrent at the center, and thus the steepness of the decay of the photocurrent as a function of lateral distance becomes smaller. It was also demonstrated that a higher intensity and a longer wavelength of constant light resulted in a higher spatial resolution [7].…”
Section: Resultsmentioning
confidence: 98%
“…To improve spatial resolution, an auxiliary illumination of constant light can be added around the modulated light [117,118,119,120]. As shown in Figure 5a, a ring-shaped constant illumination increases the photocarriers concentration, and the enhanced recombination will block the lateral diffusion of photocarriers induced by the modulated light.…”
Section: Spatial Resolutionmentioning
confidence: 99%